FeII Carbonyl Complexes Featuring Small to Bulky PNP Pincer Ligands – Facile Substitution of κ2P, N‐Bound PNP Ligands by Carbon Monoxide. Issue 30 (30th September 2015) - Glatz, Mathias; Holzhacker, Christian; Bichler, Bernhard; Mastalir, Matthias; Stöger, Berthold; Mereiter, Kurt; Weil, Matthias; Veiros, Luis F.; Mösch‐Zanetti, Nadia C.; Kirchner, Karl
Abstract: Complexes trans ‐ and cis ‐[Fe(κ 3 P, N, P ‐PNP)(CO)Cl2 ] complexes bearing sterically demanding to small PNP ligands based on the 2, 6‐diaminopyridine scaffold are synthesized. The aromatic pyridine ring and the phosphine PR2 moieties are connected through NH, N ‐alkyl, or N ‐aryl linkers. For bulky PNP ligands, with the exception of the ligands with P t Bu2 units, these complexes are obtained upon the treatment of [Fe(κ 3 P, N, P ‐PNP)Cl2 ] with CO. With small PNP ligands, such complexes are not accessible directly owing to the formation of [Fe(κ 3 P, N, P ‐PNP)(κ 2 P, N ‐PNP)Cl]Cl. These complexes liberate the κ 2 ‐ P, N ‐bound PNP ligand in the presence of CO to yield [Fe(κ 3 P, N, P ‐PNP)(CO)Cl2 ] in yields of less than 50 %. High yields are achieved by reacting FeCl2 with PNP ligands under a CO atmosphere. For structural and reactivity comparisons, [Fe(κ 3 P, N, P ‐PNP‐Ph)(κ 2 P, N ‐PN‐Ph)Cl] + was prepared, and this complex does not react with CO. In contrast to the reactions in solution, in the solid state, complexes [Fe(κ 3 P, N, P ‐PNP)Cl2 ] with NH linkers are also converted quantitatively into trans ‐ or cis ‐[Fe(κ 3 P, N, P ‐PNP)(CO)(Cl)2 ] upon treatment with CO, as indicated by a color change and by IR spectroscopy monitoring. Those with N ‐alkyl and N ‐aryl linkers did not react with CO. To rationalize why most [Fe(κ 3 P, N, P ‐PNP)Cl2 ] complexes react readily with CO but those with t Bu substituents do not, the additions of CO to [Fe(κ 3 P, N, P ‐PNP‐ i Pr)Cl2 ] and [Fe(κ 3 P, N, P ‐PNP‐ t Bu)Cl2 ] were investigated by DFT calculations. Abstract : Complexes trans ‐ and cis ‐[Fe(κ 3 P, N, P ‐PNP)(CO)Cl2 ] bearing PNP ligands in which a pyridine ring and PR2 moieties are connected through NH, N ‐alkyl, or N ‐aryl linkers are prepared. For small PNP ligands, the treatment of [Fe(κ 3 P, N, P ‐PNP)(κ 2 P, N ‐PNP)Cl] + with CO liberates the κ 2 ‐ P, N ‐bound PNP ligand and affords the desired [Fe(κ 3 P, N, P ‐PNP)(CO)Cl2 ] complexes.